Better pregnancy outcomes in women with day 2 or day 3 fresh embryo transfer when progesterone supplementation for luteal phase support is initiated on the day of oocyte retrieval - Chia-Chen Lee; Kuan-Sheng Lee; Christine Shan-Chi Chiu; Robert Kuo-Kuang Lee; Ming-Huei Lin (Taiwanese Journal of Obstetrics & Gynecology, 2025)
Objective: To analyze the pregnancy outcomes in women undergoing fresh embryo transfer (ET) with the initiation of luteal phase support (LPS) on the day of oocyte retrieval (OR) compared with LPS 1 day after OR. Materials and Methods: Overall, 872 patients underwent fresh ET at Mackay Memorial Hospital between January 2017 and August 2021. Eligible patients were divided into two cleavage-stage (day 2 or day 3) ET and day 5 elective single ET (e-SET) groups. Pregnancy outcomes were analyzed with the initiation of LPS on the OR day and 1 day after OR. The subgroup with diminished ovarian reserve (DOR) (anti-Mullerian hormone ≤1.1 ng/mL) on cleavage-stage ET group was analyzed between the two LPS initiation time points. Results: The cleavage-stage ET group that received LPS on the OR day showed significantly higher implantation (27.8 % vs. 17.6 %, p = 0.002), clinical pregnancy (46.3 % vs. 34.4 %, p = 0.022), and livebirth (33.7 % vs. 23.6 %, p = 0.037) rates. In the subgroup analysis of DOR in the cleavage-stage ET group, LPS initiated on the OR day led to significantly higher rates of implantation (30.7 % vs. 16.2 %, p = 0.048), clinical pregnancy (50.0 % vs. 26.5 %, p = 0.023), and nonstatistically significant but higher livebirth (38.6 % vs. 20.6 %, p = 0.067). In the day 5 e-SET group, no significant differences in clinical pregnancy (51 % vs. 59.4 %, p = 0.294) and livebirth (41 % vs. 44.4 %, p = 0.665) rates were found between the two LPS initiation time points. Conclusion: Women undergoing day 2 or day 3 ET appear to have better pregnancy outcomes including clinical pregnancy, livebirth, and implantation rates when LPS was initiated on the OR day than those undergoing LPS initiated 1 day after OR, particularly for women with DOR. However, in the day 5 e-SET group, clinical outcomes are comparable between the two initiation time points.